Arabic Language Competence in Tourism: Strategic Approaches and Literature Insights - Safitri, Entin; Sagala, Rumadani; Erlina, Erlina; Koderi, Koderi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The tourism industry in Indonesia holds significant potential for attracting tourists from the Middle East. However, the limited Arabic language proficiency among tourism personnel remains a key barrier to delivering high-quality services. As Arabic is an international language widely used by Middle Eastern travelers, mastering it is essential for tour guides and other stakeholders to enhance communication and service delivery. The main problems identified include the lack of relevant Arabic teaching materials tailored to tourism, insufficiently trained instructors with tourism-specific knowledge, and learning methods that are disconnected from real-world contexts. This study employs a qualitative literature review approach to examine strategies for improving Arabic language competence within the tourism sector. Specifically, it explores the use of image-based and online media as effective tools in language acquisition. Image media aids in reinforcing vocabulary retention and conceptual understanding, while online platforms such as Aljazeera and BBC Arabic provide access to up-to-date, tourism-relevant vocabulary and authentic language use. The study suggests integrating these media types into Arabic language instruction and curriculum design to align with the practical needs of the tourism industry. Findings indicate that the use of visual and online media significantly enhances learners’ vocabulary acquisition, motivation, and communicative competence. Consequently, this approach prepares tourism personnel more effectively to engage with Arabic-speaking tourists, thereby supporting the broader goals of the tourism sector. The study contributes to the field of Arabic language education by offering pedagogical insights that bridge language learning with vocational and industry-specific applications.